Price transmission mechanism in the thai rice market - Tansuchat R. (2017)
© Springer International Publishing Switzerland 2016. This study aimed to analyze price transmission in the Thai rice market using the MS-BVECM. We focused on the data set related to Thailands rice price, including Thai white rice price, Thai parboiled rice, Thai paddy price, and World rice price collected from M1/2004 to M3/2014. We estimated the model with two regimes; namely high market price regime and low market price regime. The estimated results showed that there existed some short-run relationships between these rice prices in both regimes. Unlike the long-run, there existed only one long-run relationship (one cointegrating equation) in the high market price regime expressed in the Thai white rice equation. Meanwhile, Thai paddy price has the long-run relationship and short-run adjustment dynamics in the low market price regime. In addition, we found that India’s non-basmati rice exports and the paddy price guaranteed at 15,000 THB per ton are two main reasons which caused the switching between these two regimes.